Hybrid polymer composite membrane for an electromagnetic (EM) valveless micropump. (20th June 2017) - Mohd Said, Muzalifah; Yunas, Jumril; Bais, Badariah; Hamzah, Azrul Azlan; Yeop Majlis, Burhanuddin
Abstract: In this paper, we report on a hybrid membrane used as an actuator in an electromagnetically driven valveless micropump developed using MEMS processes. The membrane structure consists of the combination of a magnetic polymer composite membrane and an attached bulk permanent magnet which is expected to have a compact structure and a strong magnetic force with maintained membrane flexibility. A soft polymeric material made of polydimethylsiloxane (PDMS) is initially mixed with neodymium magnetic particles (NdFeB) to form a magnetic polymer composite membrane. The membrane is then bonded with the PDMS based microfluidic part, developed using soft lithography process. The developed micropump was tested in terms of the actuator membrane deflection capability and the fluidic flow of the injected fluid sample through the microfluidic channel. The experimental results show that the magnetic composite actuator membrane with an attached bulk permanent magnet is capable of producing a maximum membrane deflection of up to 106 µ m. The functionality test of the electromagnetic (EM) actuator for fluid pumping purposes was done by supplying an AC voltage with various amplitudes, signal waves and frequencies. A wide range of sample injection rates from a few µ l min −1 to tens of nl min −1 was achieved with a maximum flow rate of 6.6 µ l min −1 . The injection flow rate of the EM micropump can be controlled by adjusting the voltage amplitude and frequency supplied to the EM coil, to control the membrane deflection in the pump chamber. The designed valveless EM micropump has a very high potential to enhance the drug delivery system capability in biomedical applications.